4-Octyl Itaconate Alleviates Lipopolysaccharide-Induced Acute Lung Injury in Mice by Inhibiting Oxidative Stress and Inflammation - Li Y; Chen X; Zhang H; Xiao J; Yang C; Chen W; Wei Z; Chen X; Liu J (Dove Medical Press, 2020)
Yang Li,1 Xing Chen,1 Hua Zhang,1 Jie Xiao,2 Chuanlei Yang,2 Weiqiang Chen,1 Zhanjie Wei,3 Xinzhong Chen,1 Jinping Liu4 1Department of Cardiovascular Surgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430022, Hubei, People’s Republic of China; 2Department of Cardiovascular Surgery, Central Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430014, Hubei, People’s Republic of China; 3Department of Thyroid and Breast Surgery, Central Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430014, Hubei, People’s Republic of China; 4Department of Cardiovascular Surgery, Zhongnan Hospital, Wuhan University, Wuhan 430071, Hubei, People’s Republic of ChinaCorrespondence: Jinping LiuDepartment of Cardiovascular Surgery, Zhongnan Hospital,Wuhan University, Wuhan Donghu Road 169#, Wuhan 430071, People’s Republic of ChinaTel +86-027-67812888Email liujinping@znhospital.cnXinzhong ChenDepartment of Cardiovascular Surgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430022, Hubei, People’s Republic of ChinaTel +86-027-85726114Email xinzhongchen@hust.edu.cnBackground: Acute lung injury (ALI) is a fatal disease in the absence of pharmacological treatment. Oxidative stress and inflammation are closely related to ALI. Innate immune cells are the main source of reactive oxygen species (ROS). Macrophages play an extremely important role in ALI through the activation of inflammation and oxidative stress. Itaconate, a metabolite of tricarboxylic acid, has been reported to have strong antioxidant and anti-inflammatory effects. However, the role of itaconate in ALI is unclear. Herein, we use 4-octyl itaconate (OI), the cellular permeable derivate of itaconate, to study the effects of itaconate in vivo and in vitro.Methods: We used OI to pretreat C57BL/6 mice and LPS-induced ALI models to illustrate the role of itaconate in acute lung injury. The mice were randomly divided into four groups: control group, OI (100 mg/kg) group, ALI Group, ALI + OI (50 mg/kg) group, and ALI + OI (100 mg/kg) group. RAW264.7 cells were used to further prove the role and mechanism of itaconate in vitro.Results: According to the H&E staining of the lung, OI was observed to significantly reduce lung inflammation. The active oxygen content of tissues was also significantly reduced (P< 0.05). OI reduced the accumulation of neutrophils and secretion of inflammatory factors in LPS-induced ALI (P< 0.05). At the cellular level, OI also reduced oxidative stress and inflammation. Intervention with OI was also observed to upregulate the expression of nuclear factor erythroid 2-related factor-2 (Nrf-2) and Nrf-2 target genes in the lung tissue and RAW264.7 cells.Conclusion: OI alleviates LPS-induced ALI. Moreover, the antioxidant and anti-inflammatory effects of OI might depend on the activation of Nrf-2. Therefore, OI might have therapeutic potential for the treatment of ALI.Keywords: metabolite, inflammation, reactive oxygen species, acute respiratory distress syndrome, nuclear factor erythroid 2-related factor 2, Nrf-2